Risk factors for gastric precancerous and cancers lesions in Latin American counties with difference gastric cancer risk. (February 2020) - Flores-Luna, Lourdes; Bravo, Maria Mercedes; Kasamatsu, Elena; Lazcano Ponce, Eduardo César; Martinez, Teresa; Torres, Javier; Camorlinga-Ponce, Margarita; Kato, Ikuko
Highlights: Gastric cancer remains the leading cause of infection-related cancer in 2018. 1222 patients with various gastric pathology were recruited in Latin American Seropositivity to H. pylori was associated with risk of pre-neoplastic lesions. Grain/cereal intake and egg intake were related to gastric cancer. Cigarette smoking was associated with risk of being infected by H. pylori . Abstract: Objective: To evaluate the risk factors associated with pre-neoplastic lesions and gastric cancer in countries with different cancer risk in Latin America. Methods: 1222 questionnaires of risk factors related to pre-neoplastic lesions and gastric cancer were obtained from patients from Mexico (N = 559), Colombia (N = 461) and Paraguay (N = 202), who were treated at the gastroenterology or oncology service of participant hospitals. In addition, biopsies specimens to establish histological diagnosis and blood to detect IgG antibodies against Helicobacter-pylori ( H. pylori ) whole-cell antigens and CagA protein using an ELISA were collected. These consisted of 205 gastric cancer, 379 pre-neoplastic (intestinal metaplasia (IM) / atrophic gastritis) and 638 control (normal /non-atrophic gastritis) cases. The odds ratio (OR) and 95% confidence intervals (CI) associated with potential risk factors were estimated by polynomial logistic regression model. Results: Seropositivity to H. pylori was associated with risk of pre-neoplastic lesions, with OR = 1.9 (CI 95% 1.2-2.9; p = 0.006). Grain / cereal intake (OR = 1.6, 95% CI 1.0–2.5 ; p = 0.049) and egg intake (OR = 1.7 95% CI 1.1–2.6 ; p = 0.021) were related to gastric cancer. Among, people who did not developed gastric cancer, smoking more than five cigarette per day had the highest risk of being infected by H. pylori (OR = 1.9; CI 95% 1.1–3.3 ; p = 0.028). Conclusion: The present study in Latin American countries confirmed that similar environmental factors such as smoking and grain/cereal consumption were associated with H. pylori infection and its induced gastric lesions as reported in other regions where dominant H. pylori strains differ.